1962
DOI: 10.1111/j.1476-5381.1962.tb01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of a Mixture of Amphetamine and a Barbiturate in Man

Abstract: The effects in man of a mixture of amphetamine and a barbiturate (15 mg of amphetamine sulphate and 300. mg of cyclobarbitone) and of each of the constituents separately were assessed on the performance of simple mental and motor tasks, on the pulse rate and on subjective reports. The mixture produced a pattern of effects which was different from that produced by either drug separately. It impaired the efficiency of the performance of tasks much less than did the barbiturate drug alone; it produced almost as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

1965
1965
1980
1980

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…This low dose of barbiturate was not studied by itself, but from other experiments (Nash, 1962) it seems unlikely that it would have any significant effects alone. The mixture which contained four times as much barbiturate, on the other hand produced some impairment of performances, though less than the constituent dose of barbiturate alone, and this confirmed previous findings (Legge & Steinberg, 1962). Like the first mixture and the control it produced reports of feeling " sociable," but otherwise the subjective effects were different.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This low dose of barbiturate was not studied by itself, but from other experiments (Nash, 1962) it seems unlikely that it would have any significant effects alone. The mixture which contained four times as much barbiturate, on the other hand produced some impairment of performances, though less than the constituent dose of barbiturate alone, and this confirmed previous findings (Legge & Steinberg, 1962). Like the first mixture and the control it produced reports of feeling " sociable," but otherwise the subjective effects were different.…”
Section: Discussionsupporting
confidence: 80%
“…There were few " desirable " effects, but a large proportion of subjects reported " undesirable " effects, for example that they felt dizzy, unsteady, drowsy and confused. Feelings suggesting " elation " which were prominent with this mixture in the previously reported study (Legge & Steinberg, 1962) were reported only fairly frequently by subjects in both the present mixture groups, and the effect only reached statistical significance in the Drinamyl-type mixture group as compared with cyclobarbitone alone. This may have been partly due to the different way of eliciting subjective sensations in the present investigation; the word " elated " did not seem a very natural one for the students to make use of.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The effects of such drugs range from significant improvement of performance to significant impairment of performance, depending on the particular task and drug. Oexamphetarnine, for example, has been shown to improve performance on various mental and motor tasks, including pursuit·rotor tasks (payne & Moore, 1955), mathematical reasoning tasks (Nash, 1962;Legge & Steinberg, 1962), sustained work tasks (Kornetsky, 1959), as well as on a wide variety of more specific tasks (Nash, 1962;Payne & Hauty, 1954;Lehmann & Csank, 1957). However, accuracy of setting controls (Eysenck & Easterbrook, 1960), reaction time (Lehmann & Csank, 1957), and the accuracy of certain forms of judgment (Hauty & Payne, 1957) show a decrement in performance in response to dexamphetarnine administration.…”
mentioning
confidence: 99%